Prevalence of depression and its associated factors among medical students: a study using beck depression inventory - Sharma, Ravi C.; Sharma, Dinesh Dutt; Kanwar, Neeraj; Kanwar, Pankaj; Singh, Baljeet; Singh, Mahender (International Journal of Research in Medical Sciences, 2017)
Background: Medical education carries with it a great burden of stress that can result in depression. This study was conducted to assess the prevalence of depression in medical students and various factors contributing to depression in the institute. Methods: A stratified random sample of 280 students was evaluated using Beck Depression Inventory by investigators. Associations between depression and year of study, addiction like alcohol use, family problems, family history of depression and staying away from home were analysed by univariate analysis. Results: The overall prevalence of depression was found to be 30.0%. Among those with depression, a majority (93%) had mild and moderate degree of depression. The study depicted that 41.6% (35) of the depressed were females and 58.3% (49) were males. As per the cut-off scores, 196 students (69.9%) scored as normal (0-9), 60 (21.4%) as mild (10-18), 18 (6.4%) as moderate (19-29), 4 (1.4%) as severe (30-40) and 2 (0.7%) as very severe (>40) depression. The prevalence of depression was comparatively less among 1st and 2nd year medical students (17.1%) and the difference between the grade of depression and year of study was found to be not significant (χ2=148, P=0.13). The prevalence was found more among those with family problems and family history of depression. Conclusions: In our study, depression was quite prevalent among medical students of the region. Our findings stressed the importance of broad screening and psychiatric counselling of this vulnerable population more meticulously.